2020
DOI: 10.1039/d0sc03367g
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the intricate network of molecular interactions of a hyperstable engineered biocatalyst

Abstract: Computational design of protein catalysts with enhanced stabilities for use in research and enzyme technologies is a challenging task. Using force-field calculations and phylogenetic analysis, we previously designed the haloalkane...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 77 publications
(108 reference statements)
1
35
0
Order By: Relevance
“…A recent structural study carried out on the monomer of DhaA115 revealed an intricate network of molecular interactions that reinforce the engineered αβα sandwich architecture. 26 Mutations to bulky aromatic amino acids at the protein surface trigger long-distance backbone changes through multiple cooperative interactions. These interactions produce an unprecedented double-lock system that closes the molecular gates to the active site and reduces the volumes of the access tunnels 26 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent structural study carried out on the monomer of DhaA115 revealed an intricate network of molecular interactions that reinforce the engineered αβα sandwich architecture. 26 Mutations to bulky aromatic amino acids at the protein surface trigger long-distance backbone changes through multiple cooperative interactions. These interactions produce an unprecedented double-lock system that closes the molecular gates to the active site and reduces the volumes of the access tunnels 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that the computationally-driven stabilization of a monomeric haloalkane dehalogenase DhaA115 (Tm app = 73.5°C; ΔTm app > 23°C) 5,26 unintentionally altered the protein folding landscape, resulting in the formation of stable domain-swapped intermediates. Our structural findings reveal that the intended stabilizing mutations were frequently found in the cryptic hinge regions and introduced secondary interfaces where they made new non-covalent interactions between the misfolded, intertwined polypeptide chains.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations